(untitled) (MAUSAM, 1959)
The Sq diurnal variation in H at Trivandrum and Annamalainagar are found to be large compared with those at Alibag. The quiet day range in H at Trivandrum in the month of March is abnormally large. Though the Sq variations in V at Trivandrum are not abnormal they are larger than those at Annamalainagar and Alibag. The response of the H elements to disturbance at Trivandrum, Annamalainagar as well as Alibag are similar in sense. But the V element at Annamalainagar shows a difference in its response to disturbance. When the V elements at both Alibag and Trivandrum show an increase in numerical magnitude the V element at Annamalainagar shows a decrease and vice versa. When the magnitudes of disturbance are examined they are found to be almost the same in the H element at all the observatories (including Alibag) during night hours. But during the day the magnitudes of disturbance in H element at Trivandrum and Annamalainagar are always greater than that at Alibag, a station away from the geomagnetic equator. Effects of disturbance in the V element are greatest at Trivandrum both during the day as well as the night. The lines of force of an average disturbance field in a longitudinal plane over the region of the Indian Peninsula appear to be smooth curves with their concave side turned upwards, their turning points occurring between Annamalainagar and Alibag during the day and close to Alibag in the night.